Uma Experiência de Formação Continuada com Professores de Arte e Matemática no Ensino de Geometria - Dos Santos, Marli Regina [UNESP]; Bicudo, Maria Aparecida Viggiani [UNESP] (FapUNIFESP (SciELO), 2015)
This article exposes a work for continuing education of art and mathematics teachers of basic education, focusing on the teaching of geometry through tessellations. We emphasize the constitution of a nucleus of ideas formed by sense perceived when we focus on these disciplines, explaining that, in the origin of this nucleus and expression of meanings, are evident acts as the watch, know, imagine, create and realize sizes and forms. We present the tessellations used in continuing education course, focused on the teaching of geometry, which enabled the development of activities with these different disciplines. We focus on the dialogue among teachers while they engaged in the proposed activities, highlighting our analysis: the perspective of looking; the formation and the project; and interfaces of Mathematics Education. What was shown in the experience together with the teacher, which are of the same or different disciplines, indicates the constitution of intersubjectivity that enables interdisciplinary courses to be given.
An experience of continuing education with art and mathematics teachers in teaching geometry
Keywords: Geometry; Interdisciplinarity; Mathematics Education; Phenomenology; Tessellation